Causal relationship between hepatic function indicators and thrombocytopenia risk in early-stage hepatitis B virus infection: evidence from clinical observational studies and mendelian randomization analyses - Chen, Tian-bin; Jiang, Jian-wei; Guo, Hong-yan; Chen, Xiao-tong; Zhi, Shuai; Hu, Yu-hai; Fu, Ya; Zeng, Yong-bing; Liu, Can; Ou, Qi-shui; Rao, Shi-tao (Frontiers in Immunology, 2025)
BackgroundThrombocytopenia is a common occurrence in patients with hepatitis B virus (HBV) infection, particularly in those with liver cirrhosis. However, it can also manifest in the early stages of HBV infection, before the onset of liver cirrhosis. Despite its prevalence, the molecular mechanisms underlying thrombocytopenia in this context are not well understood. Therefore, the primary aim of this study was to investigate whether common hepatic function indicators have a significant causal role in this mechanism.MethodsWe conducted a retrospective examination of the association between HBV infection and thrombocytopenia risk in apparently healthy participants who underwent health screening examinations. Subsequently, we investigated the causal relationship between multiple hepatic function indicators and thrombocytopenia risk by integrating clinical observational studies and univariate/multivariate Mendelian randomization (MR) analyses.ResultsAmong 16,464 participants who underwent health screening examinations, 2,730 subjects (16.58%) tested positive for HBsAg. The prevalence of thrombocytopenia was significantly higher in HBsAg-positive subjects compared to healthy controls (P<0.001). Univariate and stepwise multivariate logistic regression analyses identified lower albumin and higher alanine aminotransferase (ALT), alkaline phosphatase, and total bilirubin levels as independent factors significantly associated with thrombocytopenia risk (OR=1.95~6.60). Univariate and multivariate MR analyses further confirmed that ALT had significant causal effects on thrombocytopenia risk (adjusted P<0.05). Notably, we also observed significant trends of a higher prevalence of thrombocytopenia with elevated ALT levels in both the clinical raw and propensity score matching cohorts (P=0.015 and 0.014, respectively).ConclusionsThis study identified multiple hepatic function indicators as independent factors associated with thrombocytopenia risk. Notably, our findings provided the first dual confirmation of the causal effect of the injury indicator ALT on thrombocytopenia risk, as evidenced by both clinical observational studies and genetics-based MR analyses, prior to the development of liver cirrhosis.